Innate Immune Signaling and Proteolytic Pathways in the Resolution or Exacerbation of SARS-CoV-2 in Covid-19: Key Therapeutic Targets? - Sallenave, Jean-Michel; Guillot, Loïc (Frontiers in Immunology, 2020)
COVID-19 is caused by the Severe Acute Respiratory Syndrome (SARS) coronavirus (Cov)-2, an enveloped virus with a positive-polarity, single-stranded RNA genome. The initial outbreak of the pandemic began in December 2019, and it is affecting the human health of the global community. In common with previous pandemics (Influenza H1N1 and SARS-CoV) and the epidemics of Middle east respiratory syndrome (MERS)-CoV, CoVs target bronchial and alveolar epithelial cells. Virus protein ligands (e.g., haemagglutinin or trimeric spike glycoprotein for Influenza and CoV, respectively) interact with cellular receptors, such as (depending on the virus) either sialic acids, Dipeptidyl peptidase 4 (DPP4), or angiotensin-converting enzyme 2 (ACE2). Host proteases, e.g., cathepsins, furin, or members of the type II transmembrane serine proteases (TTSP) family, such as Transmembrane protease serine 2 (TMPRSS2), are involved in virus entry by proteolytically activating virus ligands. Also involved are Toll Like Receptor (TLR) family members, which upregulate anti-viral and pro-inflammatory mediators [interleukin (IL)-6 and IL-8 and type I and type III Interferons among others], through the activation of Nuclear Factor (NF)-kB. When these events (virus cellular entry and innate immune responses) are uncontrolled, a deleterious systemic response is sometimes encountered in infected patients, leading to the well-described “cytokine storm” and an ensuing multiple organ failure promoted by a downregulation of dendritic cell, macrophage, and T-cell function. We aim to describe how the lung and systemic host innate immune responses affect survival either positively, through downregulating initial viral load, or negatively, by triggering uncontrolled inflammation. An emphasis will be put on host cellular signaling pathways and proteases involved with a view on tackling these therapeutically.